Need Analysis Course Design: ESP Textbook Evaluation in The Psychology Faculty - Yulis Setyowati; Ari Astutik; Shanty AYPS (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2023)
This study aims to describe the 'need analysis' of English for Psychology courses and evaluate the ESP textbook from the point of view of the textbook users at the Faculty of Psychology. A need analysis survey in learning ESP and ESP textbook evaluation was conducted and then analyzed quantitively. The data sources of this research were students of the Faculty of Psychology who were taken by purposive sampling, which amounted to 20 people already in the 4th, 6th, and 8th semesters, the head of the Psychology department, and three lecturers in the Psychology Faculty. The data collection used was a questionnaire and documentation. The data is in the form of questionnaire results and interviews. Documentation technique is used in collecting data, while analysis technique is used in analyzing data, namely reduction, data display, and drawing conclusions and verification. The study results show that language skill materials are crucial for future Psychology students. Regarding speaking skills, students primarily require resources for conversing with current issues that are up-to-date. Regarding the students' need to access psychology journals and textbooks, writing and skills in composing scientific articles, reports, and lab documents are essential. However, the study reveals dissatisfaction among Psychology students with the current ESP textbook, particularly in appearance, visuals, design, layout, and writing materials. Despite some elements meeting their needs, such as layout, content, exercises, and speaking resources, improvements are needed in certain areas. Consequently, it is recommended that the ESP textbook be enhanced to better cater to these requirements, and future researchers undertaking similar studies should consider this focus on English for Specific Purposes (ESP).